PENGARUH STORE ATHMOSPHERE DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN PADA CAFE NOTIZ HUT BANDAR LAMPUNG - Mustaqim, Arif Hudal; Adinata, Yovan Ferdian; Suryani, Asri; Sanjaya, Vicky F (Faculty of economcs Universitas Singaperbangsa Karawang, 2022)
This research aims to investigate the impact of two crucial factors, namely store atmosphere and product quality, on customer loyalty in the culinary industry. Store atmosphere and product quality are identified as key factors influencing consumer behavior and shaping the level of customer loyalty. Store atmosphere encompasses visual, auditory, and olfactory elements such as Store Exterior, General Interior, Store Layout, and Interior Display, creating a unique shopping experience within the establishment. Meanwhile, product quality refers to the standards and customer satisfaction regarding features like Performance, Conformance, Features, Reliability, and Aesthetics. This study adopts a quantitative approach, utilizing an online questionnaire through Google Forms as the data collection tool from respondents who are customers of Cafe Notiz Hut in Bandar Lampung. The collected data will be analyzed using relevant statistical methods to examine the relationships between store atmosphere, product quality, and customer loyalty. Control variables such as pricing will also be considered in the analysis to ensure accurate and reliable results. The anticipated outcomes of this research are expected to provide in-depth insights into the extent to which store atmosphere and product quality can influence customer loyalty. The practical implications of these findings will assist stakeholders in the culinary industry in developing more effective marketing strategies and enhancing the overall customer experience. Additionally, this study may serve as a foundation for further research in different contexts or by considering additional variables that could impact customer loyalty.